The effects of nesfatin‐1 in the paraventricular nucleus on gastric motility and its potential regulation by the lateral hypothalamic area in rats. (18th November 2014) - Guo, Fei‐fei; Xu, Luo; Gao, Sheng‐li; Sun, Xiang‐rong; Li, Zhi‐ling; Gong, Yan‐ling
Abstract The current study investigated the effects of nesfatin‐1 in the hypothalamic paraventricular nucleus (PVN) on gastric motility and the regulation of the lateral hypothalamic area (LHA). Using single unit recordings in the PVN, we show that nesfatin‐1 inhibited the majority of the gastric distention (GD)‐excitatory neurons and excited more than half of the GD‐inhibitory (GD‐I) neurons in the PVN, which were weakened by oxytocin receptor antagonist H4928. Gastric motility experiments showed that administration of nesfatin‐1 in the PVN decreased gastric motility, which was also partly prevented by H4928. The nesfatin‐1 concentration producing a half‐maximal response (EC50) in the PVN was lower than the value in the dorsomedial hypothalamic nucleus, while nesfatin‐1 in the reuniens thalamic nucleus had no effect on gastric motility. Retrograde tracing and immunofluorescent staining showed that nucleobindin‐2/nesfatin‐1 and fluorogold double‐labeled neurons were observed in the LHA. Electrical LHA stimulation changed the firing rate of GD‐responsive neurons in the PVN. Pre‐administration of an anti‐ nucleobindin‐2/nesfatin‐1 antibody in the PVN strengthened gastric motility and decreased the discharging of the GD‐I neurons induced by electrical stimulation of the LHA. These results demonstrate that nesfatin‐1 in the PVN could serve as an inhibitory factor to inhibit gastric motility, which might be regulated by the LHA.<boxed-text content-type="graphic" id="jnc12973-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Nesfatin‐1 regulated the gastric distension (GD)‐responsive neurons and reduced gastric motility in the paraventricular nucleus (PVN), which were partly blocked by H4928. Electrical stimulation of the lateral hypothalamic area (LHA) increased the firing activities of GD‐responsive neurons in the PVN and promoted the gastric motility. NUCB2/nesfatin‐1/fluorogold double‐labeled neurons were identified in the LHA, indicating that nesfatin‐1 in the PVN could play a pivotal role in the central control of gastric motility and the LHA may participate in the regulatory process. NUCB2 = nucleobindin‐2